Monitoring and Controlling Temperature Egg Incubator Prototype Based LoRa Communication - Mas Aly Afandi; Fadhila Karin Purnomo; Raditya Artha Rochmanto; Sevia Indah Purnama (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
Poultry industries encounter problem in produce day old chicken (DOC). Poultry industries usually produce DOC using egg incubator. Egg incubator must have high accuracy in reading environment temperature inside the machine. The temperature environment inside the egg incubator machine needs to keep in range 36°C - 40°C. On the other hand, hatcheries and chicken coop usually not in one place. Poultry industries require applied technology to solve this problem. This problem can be solved by using internet of things. But internet of things can be so expensive. This research is aim to implement monitoring and controlling temperature inside egg incubator prototype while using low-cost communication technology. Research result showed that the control system could maintain egg incubator prototype temperature in optimal range with an accuracy of 99,63%, 99,83%, 99,97%,99,64%, and 99,37% when reading a temperature of 36°C, 37°C, 38°C, 39°C, and 40°C respectively. This research implements Long Range (LoRa) technology for monitoring system. Different with internet of things technology, point to point LoRa communication does not needs payment to communicate but still provide wide area communication. According to research result, point to point LoRa communication provide good performance in sending temperature data in range area 50m, 100m, 150m, 200m, 250m, and 300m with good average Receive Signal Strength (RSSI). This research can conclude proposed egg incubator can keep temprature in optimal range. Proposed incubator also can communicate properly to send data temperature for monitoring temperature.